Comparison between the Wilhelmy surface tension measurement method and the pendant drop shape analysis method - Estela Cristina Cavalcante de Farias; Ricardo Kropf Santos Fermam; Amsterdam de J. Souza Marques de Mendonça (Acta Polytechnica, 2025)
Surface tension plays an essential role in various laboratory and industrial processes. The Fluid Metrology Laboratory (Laflu) of the National Institute of Metrology, Quality and Technology (Inmetro) uses the Wilhelmy and DuNoüy methods and has a tensiometer for determining surface tension by the drop shape analysis method in use. One way to ensure the reliability of surface tension measurement results is to compare the methods used. A comparison was made between the Wilhelmy method and the drop shape analysis method. The comparison involved measurements of the surface tension of these liquids: bidistilled water, n-dodecane, and Perfluorocarbon (FC-40), and used the calculation of the Normalized Error (EN), presenting results according to acompatible criterion. Analysing the uncertainties involved, the contribution of the uncertainty of the regression used in the correction of the tensiometer indication was the most relevant.